Media strategies of professional football clubs - Bekurov, Ruslan Viktorovich; Lingzhi, Lai; Maryna, Lyudmila Petrovna (Theory and Practice of Physical Culture, 2022)
Article attempts to analyze the functionality of club media of leading Russian and European football clubs. In particular, the material includes a reasoned, case-based assumption about the need for a media component in the structures of such organizations, regardless of their status. The concept of the article was determined by fundamental and applied research in the field of sports communications and sports journalism. These include the works of K. Alekseev and S. Ilchenko, S. Mikhailov and A. Mostov, E. Votik, M. Danilova, M. Vishnevsky, I. Tkachev, I. Lyulevich and V. Kostikov. The interdisciplinary nature of the study led to the application of a systematic approach using the method of analysis (structural and comparative) and generalization. The authors identify the status of football clubs as subjects of sports media communication, review the media assets of football clubs in Russia and abroad, identify the main channels and tools of interaction between clubs and fans. The main conclusion is the thesis about the inevitability of the functioning of a modern football club as an effective media company, including for the construction and development of a club brand.